The History and Evolution of the Integration of Medical Education into the Field of Healthcare Services (Healthcare Network) of the Islamic Republic of Iran - Seyyed Alireza Marandi (Strides in Development of Medical Education)
Background: In Iran, the shortage of medical workforce in the population has caused the health of people to be exposed to many risks in different parts of the country, especially in deprived areas. Therefore, in 1983, the plan for “Integrating Education and Research in Health Care and Services” was presented by the Supreme Council of the Cultural Revolution and approved in 1985 after some amendments.Objectives: This article reviews the history and evolution of the "Integration of Education and Research in Health Care and Services" project.Methods: The library study method (reviewing reliable sources in domestic and international publications, using the study keywords), recording the author's personal experiences, and content analysis were used.Results: All quantitative indicators (such as the number of educational centers and student admission capacities) qualitative indicators (such as the level of accountability and social commitment of academics and the health culture of the community) and general health indicators in the country were improved.Conclusion: Integrating education and research in health care and services is a revolutionary and beneficial achievement in the country and an inspiring experience for all health systems in the world. If generalized and deepened, it can become the most prominent contemporary healthcare experience in the world.